Amine detection with distyrylbenzenedialdehyde-based Knoevenagel adducts - Kumpf, Jan; Schwaebel, S. Thimon; Bunz, Uwe H. F. (The journal of organic chemistry, 2015)
Eight acceptor-substituted distyrylbenzene (DSB) derivatives were obtained by postfunctionalization of dialdehyde precursor 1 using Knoevenagel condensation. Solubility in a water/THF 9:1 mixture was achieved through the addition of branched oligoethylene glycol side chains. The acceptor compounds discriminate primary and secondary amines in aqueous solution. The fluorescence responses were analyzed by the multivariate analysis of variance (MANOVA) protocol, a statistical tool. In contrast to 1, the adducts show reactivity toward secondary and aromatic amines. Nitroolefin 2f is the most active dosimeter molecule. Reaction with amines is completed after less than 3 min, and the limit of detection (LOD) is improved by a factor of 10. Propylenediamine can be detected at 75 μM. This is a 10-fold improvement for the detection limit when compared to the detection limit of the starting dialdehyde.
Gesehen am 03.06.2020